Management of Chemotherapy-Induced Left Ventricular Dysfunction and Heart Failure in Patients With Cancer While Undergoing Cancer Treatment: The MD Anderson Practice - Fadol, Anecita P. (Frontiers in Cardiovascular Medicine, 2018)
Chemotherapy-induced cardiotoxicity resulting in heart failure (HF) is one of the most dreaded complications of cancer therapy that can significantly impact morbidity and mortality. With a high prevalence of cardiovascular disease in cancer patients, the risk of developing HF is significantly increased. A new discipline of Onco-Cardiology has evolved to address the cardiovascular needs of patients with cancer, however, there is limited evidence-based data to guide clinical decision-making in the management of the cardiovascular complications of cancer therapy. The department of cardiology at MD Anderson Cancer Center initiated the MD Anderson Practice (MAP) project and developed algorithms to guide the management of the cardiovascular complications of cancer therapy. For chemotherapy-induced HF, we initiated the Heart Success Program (HSP), a patient-centered program that promotes interdisciplinary collaboration for the management of concurrent HF resulting from chemotherapy-induced cardiotoxicity. After one year of HSP implementation, compliance with the Center for Medicare and Medicaid Services HF core measures has significantly improved. The measurement of LVEF and initiation of recommended pharmacologic therapy for HF (angiotensin converting enzyme inhibitor [ACE-I] or angiotensin receptor blocker for ACE-I intolerant patients) has improved to 100%; provision of discharge instruction has improved from 50% to 94%; and the 30-day hospital readmission rate decreased from 40% to 27%. This article will describe the MD Anderson Practice in the management of chemotherapy-induced cardiomyopathy and HF in cancer patients through the HSP. The novelty of the HSP has raised clinician’s awareness of the magnitude of the clinical problem of HF in cancer and the